Beyond the Screen: Immersive Analytics with Augmented Reality/Virtual Reality - Parab, Amey (International Journal of Computing and Engineering, 2025)
Immersive analytics is a paradigm shift in data visualization that uses Augmented Reality and Virtual Reality technology to build three-dimensional spaces in which the user can intuitively explore complex data sets by spatial awareness and physical interaction methods. The replacement of traditional two-dimensional interfaces with immersive environments is the basic limitation of traditional analysis tools, which are replaced by unified environments that allow analysts to simultaneously have a global perspective of data patterns and drill down to areas of focus. Recent advancements in WebXR APIs and frontend frameworks have allowed for advanced cross-platform solutions that connect web technologies with various AR/VR hardware systems, enabling browser-based immersive analytics applications without the need for specialized software installations. Comprehensive assessment in scientific, educational, and industrial sectors shows uniform enhancements in spatial awareness, pattern detection, and teamwork in problem-solving tasks when contrasted with conventional dashboard interfaces. Technical architecture executions integrate sophisticated rendering pipelines, multi-modal interaction frameworks, and performance enhancement strategies that facilitate real-time handling of extensive datasets in resource-limited settings. Applications include molecular visualization, climate modeling, business intelligence, and educational settings, demonstrating improved analytical efficacy via physical interaction methods and three-dimensional data displays. Nonetheless, considerable obstacles persist, such as hardware restrictions, accessibility issues, integration difficulties, and organizational resistance that affect the broad implementation viability in both enterprise and educational settings.